The PEMANFAATAN DIGITAL MARKETING UNTUK MENINGKATKAN PENDAPATAN PADA MASA PANDEMI COVID-19 PADA PANHEAD CAFE - Meiriasari, Vhika; Lady Havivi, Siti (Universitas katolik Musi Charitas, 2020)
The purpose of this activity is to increase income at Panhead Cafe which is a culinary business that was opened just at the time of the co-19 pandemic. The method used is a participatory approach such as focus group discussions, interviews, consultation, determining solutions, conducting training and evaluating and monitoring. The digital marketing strategy chosen is social media marketing by creating a Panhead Cafe account on Instagram, Facebook and online ordering media panheadcafe.antarinmakan.com. The results of the activity can be seen with an increase in take away sales after creating an account on social media and online ordering media. Digital Marketing or Digital Marketing, now is a must for all companies and is an effective marketing strategy. Keywords : Digital Marketing, Social Media Marketing